A novel uveitis model induced by lipopolysaccharide in zebrafish - Xiao, Xiao; Liu, Zhangluxi; Su, Guannan; Liu, Huan; Yin, Wenhui; Guan, Yuxuan; Jing, Shixiang; Du, Liping; Li, Fuzhen; Li, Na; Yang, Peizeng (Frontiers in Immunology, 2022)
Endotoxin-induced uveitis (EIU) served as an important tool to simulate uveitis. In this study, EIU was for the first time successfully induced in zebrafish following intravitreal LPS injection. For zebrafish inflamed eyes, we measured the dynamic changes at histopathological and transcriptomic levels, and green fluorescent protein (GFP)-positive area in retinal flat mounts after prednisone immersion. Histological changes and optical coherence tomography (OCT) indicated inflammation appeared at 4 hours post injection (hpi), and reached its peak at 24 hpi, then resolved at 72 hpi. Immunofluorescence confirmed that massive influx of neutrophils into the iris and vitreous body, and activation of microglia as evidenced by ameboid-shaped appearance in the retina. Retinal RNA-seq during the EIU course identified four gene clusters with distinct expression characteristics related to Toll-like receptor signaling pathway, cytokine-cytokine receptor interaction, NOD-like receptor signaling pathway, and extracellular matrix (ECM)-receptor interaction, respectively. Prednisone immersion inhibited the inflammatory response of EIU in zebrafish, which was confirmed by decreased neutrophils detected in flow cytometry and retinal flat mounts. This zebrafish EIU model may be particularly useful for gene-editing and high-throughput screening of new drugs for the prevention and treatment of uveitis.